Dynamic Rocker-Bogie: A Stability Enhancement for High-Speed Traversal - Hong-an Yang; Luis Carlos Velasco Rojas; Changkai Xia; Qiang Guo (Institute of Advanced Engineering and Science, 2014)
The rocker-bogie suspension mechanism it’s currently NASA’s favored design for wheeled mobile robots, mainly because it has robust capabilities to deal with obstacles and because it uniformly distributes the payload over its 6 wheels at all times. Even though it has many advantages when dealing with obstacles, there is one major shortcoming which is its low average speed of operation, making the rocker-bogie system not suitable for situations where high-speed traversal over hard-flat surfaces is needed to cover large areas in short periods of time, mainly due to stability problems. This paper proposes to increase the stability of the rocker-bogie system by expanding its support polygon, making it more stable and adaptable while moving at high speed, but keeping its original robustness against obstacles: One rocker-bogie system, two modes of operation.